Rescue the Food: Building a Sustainable Food System for a Nourished Future - Faza, Farah; Hardiyanti, Marina; Witaningrum, Riani; Ermamilia, Aviria (Universitas Airlangga, 2026)
Introduction: The national food security system ensures availability and stability, yet inequitable access and food utilization contribute to malnutrition and obesity. To achieve sustainable food security and SDG 2030 goals, education and redistributing surplus food can enhance community awareness and reduce food loss and waste (FLW). Aims: To initially assess community needs and evaluate an interprofessional-based educational program on sustainable food systems and nutrition security known as